2008
DOI: 10.1080/09687760802526715
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the role of background music in IVWs for learning

Abstract: Empirical evidence is needed to corroborate the intuitions of gamers and game developers in understanding the benefits of Immersive Virtual Worlds (IVWs) as a learning environment and the role that music plays within these environments. We report an investigation to determine if background music of the genre typically found in computer-based role-playing games has an effect on learning in a computer-animated history lesson about the Macquarie Lighthouse within an IVW. In Experiment 1, music stimuli were create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This research found that, for one particular musical stimulus, the number of accurately memorised facts was significantly higher. The authors suggest that this piece of music may have been more congruent with the material being taught, hence the improvement in fact recall with this particular background music (Richards et al 2008). …”
Section: Virtual Learning Environmentsmentioning
confidence: 97%
See 1 more Smart Citation
“…This research found that, for one particular musical stimulus, the number of accurately memorised facts was significantly higher. The authors suggest that this piece of music may have been more congruent with the material being taught, hence the improvement in fact recall with this particular background music (Richards et al 2008). …”
Section: Virtual Learning Environmentsmentioning
confidence: 97%
“…In an Education context, Immersive Virtual Worlds have been investigated to verify if they are an appropriate medium for learning (Richards et al 2008). Here, researchers considered how music from computer game soundtracks affects learning, specifically remembering facts.…”
Section: Virtual Learning Environmentsmentioning
confidence: 99%
“…The music industry, as part of the broader "experience design", impacts our everyday life. Music is tightly integrated with different virtual-immersive environment technologies for different purposes, e.g., education [15], gaming [37]. The main goal of background music is to create distinct and cohesive musical identities.…”
Section: Related Work 21 Background Music Industrymentioning
confidence: 99%
“…In order to study the effect of background music in virtual environments for learning Richards et al [15], it was created a specific environment for a history lesson. Results revealed that listening to the soundtrack of 'Oblivion' conducted to an improvement in the number of facts remembered by the participants.…”
Section: Background Musicmentioning
confidence: 99%